Research in Practice - An exercise in generative urban massing - Pitts, G.; Farley, H.; Datta, Sambit (Research Publishing Services, Singapore, 2013)
The following paper explores practice based research as a means of identifying issues within current urban design methods. It considers the application of parametric systems as a means of addressing these issues. These systems are developed and tested across both Australian and international urban design projects within Grimshaw Architects. A methodology is proposed for the development and application of these parametric tools across multiple scales of design resolution. It reports on the application of a set of parametric urban scale massing tools in real world design projects. This exploration is carried out in distinct phases of design defined by the scale of resolution. The phasing allows for discrete problems to be addressed more effectively at different stages of the design process while still encouraging a seamless, bi directional workflow through a digital master model.